How does earnings management impact annual report readability? - Dau, Nam Huong; Nguyen, Duy Van; Diem, Hai Thi Thanh (International Journal of Applied Economics, Finance and Accounting, 2024)
This research investigates the relationship between earnings management and annual report readability for companies listed on the Singapore Stock Exchange (SGX). Research on earnings management (EM) and the ability to read the annual report play a crucial role for investors as well as other stakeholders. The extent of earnings management can be determined based on annual reports. The analysis is based on the data of 251 domestic companies listed on the SGX from 2016 to 2021. Regression analysis of panel data was conducted using STATA version 15 software in this research. The result shows that companies with more aggressive earnings management tend to make annual reports more complex and, hence, less readable. In addition, the study also shows that the impact of earnings management on the annual report readability for enterprises of different sizes, profits, ages, and levels of financial distress is the same. Theoretically, the findings of this research for a developed financial market in Asia (Singapore) further confirm and reinforce the findings about the relationship between earnings management and report readability. In addition, one may draw important practical implications for investors as well as stakeholders in general; in particular, stakeholders may have more evidence for suspicions about earnings management whenever the annual reports become more difficult to read and understand.